Increasing the Competitiveness of the Thai Electrical and Electronics Industry in the Digital Economy Era - Sawangrat, Nilawan (Journal of Management Science Chiangrai Rajabhat University, 2024)
The objectives of this research are as follows: 1) To study the structure and operational characteristics of the Thai electrical and electronics industry in the digital economy era. 2) To study the components of enhancing the competitiveness of the Thai electrical and electronics industry in the digital economy era. 3) To develop a structural equation model (SEM) for enhancing the competitiveness of the Thai electrical and electronics industry in the digital economy era. 4) To obtain guidelines for increasing the competitiveness of the Thai electrical and electronics industry in the digital economy era. The study employed a mixed-methodology approach. The qualitative research involved in-depth interviews with a sample of 9 experts from 3 different groups. For quantitative research, data was collected via surveys from 500 entrepreneurs or executives and analyzed using frequency, percentage, average, standard deviation, and structural equation modeling (SEM) with the advanced statistical analysis software AMOS. The research of organizations found that they have been operating for 10-15 years, are Thai-owned, use financial institutions for funding, are established as limited companies, and mostly located in Thailand. There is a decentralized management. Additionally, which focus on training of employees. Leadership development at various levels is emphasized. Technology and innovation are used to enhance productivity. There is a clear and structured operational management system. A factor influencing competitiveness is the bargaining power of buyers. The research findings reveal that the level of importance of each element to increase competitiveness. When considering individual aspects, all aspects are highly significant. Human capital potential is the most important, followed by the Learning organization, Dynamic capabilities, and Competitiveness capability. Development of structural equation modeling (SEM) to increase competitiveness. All elements are related in a positive direction. This finding is statistically significant at the 0.001 level and is consistent with all the hypothesized assumptions. Furthermore, guidelines for increasing found that these four components are crucial are crucial for effectively improving the competitiveness. This finding aligns with empirical data in theoretical contexts.